Exploring alternative education: a comparison on 3 levels—Waldorf charters, non-Waldorf charters, and local public schools, as measured by the California Assessment of Student Performance and Progress - Telfer-Radzat, Kimberly (Frontiers in Education, 2024)
As the number of students enrolled in charter schools grows across the country, so do questions about their impact on academic outcomes (National Center for Educational Statistics). Given the importance of student test scores as evidence of success at the state, school, classroom, and teacher levels, understanding the effect of these charter schools' pedagogies on student outcomes is critical. Waldorf-inspired charter schools are one such growing alternative pedagogy. This study answers the question: Is there any significant difference between the levels of achievement for students in English Language Arts and math who are enrolled in Waldorf-inspired charter schools vs. those in either local public school classrooms or other charter classrooms that do not use the Waldorf pedagogy? Using OLS multiple linear regression this study examined the significance of the levels of achievement in English Language Arts (ELA) and math among students in 16 Waldorf-inspired charter schools and other charter and non-charter schools in California, using the California Assessment of Student Performance and Progress (CAASPP) scores. The research revealed that there are significantly higher percentages of eighth-grade students in Waldorf-inspired charter schools meeting or exceeding state standards in ELA and math as compared to their non-Waldorf charter school comparison groups, even when controlling for the size of the school, socioeconomic status, and district-level fixed effects (p < 0.01). This is despite the significantly smaller percentage of students in these schools meeting state standards in grades three through five. The results of this study suggest that Waldorf's developmental approach to education can result in strong academic outcomes despite a slower, low-stakes approach to teaching.